The Effects of Positive End-Expiratory Pressure on Transpulmonary Pressure and Recruitment–Derecruitment During Neurally Adjusted Ventilator Assist: A Continuous Computed Tomography Study in an Animal Model of Acute Respiratory Distress Syndrome - Widing, Carl Hannes; Pellegrini, Mariangela; Larsson, Anders; Perchiazzi, Gaetano (Frontiers in Physiology, 2019)
Background: Whether spontaneous breathing should be used in early acute respiratory distress syndrome (ARDS) is questioned, as it may cause ventilator induced lung injury (VILI), by tidal high strain/stress and recruitment/derecruitment. However, spontaneous breathing has shown beneficial effects, when used appropriately. We hypothesized that high levels of positive end-expiratory pressure (PEEP), during assisted spontaneous breathing, would prevent tidal recruitment/derecruitment (R/D), reducing ventilatory variation and respiratory rate, while potentially increasing transpulmonary pressure. The aim was to test this hypothesis in experimental mild ARDS during continuous spontaneous breathing, using neurally adjusted ventilator assist (NAVA) and uninterrupted computed tomography (CT) exposure. Methods: Mild experimental ARDS (PaO2/FiO2-ratio of 250) was induced in anesthetised pigs (n=5), ventilated using uninterrupted NAVA. PEEP was changed in steps of 3 cmH2O, from 0 to 15 and back to 0 cmH2O. Dynamic CT scans, ventilatory parameters and oesophageal pressure were acquired simultaneously. Transpulmonary pressure (PTP) and R/D were calculated and compared amongst PEEP levels. Results: When increasing PEEP from 0 to 15 cmH2O, tidal R/D decreased from 4.3±5.9% to 1.1±0.7% (p < 0.01), breath-to-breath variability decreased, while PTP increased from 11.4±3.7 to 29.7±14.1 cmH2O (R² = 0.96). Conclusions: This study shows that injurious phenomena like R/D and high PTP are present in NAVA at the two extrema of the PEEP spectrum. Willing to titrate PEEP in order to limit these phenomena, the physician must choose the best compromise between restraining the recruitment-derecruitment or the transpulmonary pressure.